2016
DOI: 10.3892/mco.2016.1019
|View full text |Cite
|
Sign up to set email alerts
|

Primary malignant pericardial mesothelioma with increased serum mesothelin diagnosed by surgical pericardial resection: A case report

Abstract: Abstract.A 37-year-old female smoker without a history of exposure to asbestos was referred to our hospital with persistent pericardial effusion. Chest computed tomography imaging examination revealed an irregular thickened pericardium with large amounts of pericardial effusion and a small pleural effusion. Fluorodeoxyglucose (FDG) positron emission tomography imaging demonstrated intrapericardial FDG accumulation. Blood tests revealed an increase in serum mesothelin levels. Examination of a surgically resecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
(9 reference statements)
0
3
0
2
Order By: Relevance
“…Serum mesothelin is considered to be the best biomarker of malignant pleural mesothelioma. Magnetic resonance imaging and fluorodeoxyglucose positron emission tomography scans are helpful for the diagnosis or staging of PMPM ( 8 - 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Serum mesothelin is considered to be the best biomarker of malignant pleural mesothelioma. Magnetic resonance imaging and fluorodeoxyglucose positron emission tomography scans are helpful for the diagnosis or staging of PMPM ( 8 - 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Хотя каких-либо специфических биомаркеров ПМТП до настоящего времени не выявлено, в по-следнее время при подозрении рекомендуется ис-следование мезотелина -сывороточного биомар-кера злокачественной мезотелиомы плевры [28], уровень которого коррелирует также с возникно-вением и динамикой ПМТП (повышение уровня при прогрессирующем течении заболевания и вре-менное снижение после хирургического удаления опухоли и начала химиотерапии) [29].…”
Section: Discussionunclassified
“…Лучевая терапия при ПМТП малоэффективна, но может применяться как дополнительное лечение у больных с неполной резекцией ПМТП [30]. И, наконец, так как удлинение жизни описано при применении химиотерапии (комбинации циспла-тина и пеметрекседа) у больных злокачествен-ной мезотелиомой плевры, такое лечение (в том числе с заменой цисплатина на карбоплатин, для уменьшения кардиотоксичности) рассматривает-ся как терапия первой линии при ПМТП, способ-ствующая увеличению продолжительности жиз-ни [1, 2,29].…”
Section: Discussionunclassified
“…Primary malignant pericardial mesothelioma (PMPM) is a rare malignant tumor with a poor prognosis. Its atypical clinical symptoms and imaging characteristics lead to misdiagnoses and inconclusive diagnoses, and its final diagnosis mainly relies on pericardial histopathology, postoperative pathology, or even autopsy results (1)(2)(3). In this article, we report the case a 50-year-old woman with PMPM that atypically presented as constrictive pericarditis to raise awareness of this easily neglected malignant pericardial tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous studies have reported that it has a misdiagnosis rate of approximately 35%, and it is most commonly misdiagnosed as tuberculous pericarditis (6). Misdiagnoses and inconclusive diagnoses may be made for the following reasons: (I) there are no specific clinical symptoms and imaging findings for some diffuse lesions; (II) the symptoms are relieved by cardiac therapy, diuretics, or pericardiocentesis, which may mask the true conditions of the disease; and (III) a pericardial biopsy is relatively hard to achieve, and pericardial effusion cytology has a low positive rate <30% in the detection of malignant cells (2,3,6).…”
mentioning
confidence: 99%